Managing online programming lab using CodeZinger - Noor Faridatul Ainun Zainal; Zarina Shukur; Kauthar Mohd Daud; Shahrina Shahrani; Masura Rahmat; Azura Ishak; Rohizah Abd Rahman (Penerbit Universiti Kebangsaan Malaysia, 2023)
Introductory programming is a basic course compulsory for students majoring in computer studies. This course is considered a difficult course to learn since time immemorial. Starting from 2020, measures taken by the Malaysian government in dealing with the COVID-19 pandemic has resulted in the educational institutions to be closed to students and face-to-face lessons replaced with online classes. Therefore, the process of learning programming becomes increasingly difficult since the instructors are unable to have face-to-face interaction with neither their local nor their international students during online classes. This paper aims to implement CodeZinger, used as an initiative to replace physical laboratory classes, and is used in monitoring the students’ achievement. In this study, the application of CodeZinger was made on two programming courses involving 266 students of Year 1, namely students taking the Computer Programming course (semester 1), and Data Structure course (semester 2). The diverse test data provided by the instructors made the students more skilful and critical in doing programming, and easier for students due to the automatic assessment function provided in CodeZinger. This study’s findings greatly influence students’ motivation in learning programming, considering that CodeZinger allows prompt feedback and automatic assessment. Moreover, for the instructors’ view of point, CodeZinger allows instructors to manage and identify students who need extra assistance in programming. In conclusion, CodeZinger assisted the students in optimizing the management of learning programming where CodeZinger provides the solution for problems and obstacles in face-to-face learning, facilitated the students in learning at their own pace, and facilitated the instructors in monitoring the students’ tasks.